Process design and evaluation of value-added chemicals production from biomass - Go, A-Ra; Ko, Jae Wook; Lee, Sang Jun; Kim, Seung Wook; Han, Sung Ok; Lee, Jinwon; Woo, Han Min; Um, Youngsoon; Nam, Jaewook; Park, Chulhwan (한국생물공학회, 2012)
Three different biodiesel production processes were simulated using the SuperPro Designer program. The process for producing biodiesel from soybean oil and methanol was designed using commercial chemical catalysts. This chemical process was compared with the biological process catalyzed by immobilized enzymes. In addition, a hybrid process consisting of catalytic biodiesel production and enzymatic glycerol carbonate production was designed and simulated for the conversion of waste glycerol to value-added chemical. Finally, the economics and productivity of these processes were evaluated to determine economic feasibility.